2021
DOI: 10.1037/tep0000308
|View full text |Cite
|
Sign up to set email alerts
|

Bug-in-the-eye supervision: A critical review.

Abstract: An important part of clinical supervision is the manner in which supervisors obtain information about what happens in trainees' treatment sessions. Research has shown that direct observation of sessions is more effective than relying on subjective report alone, and that live observation with concurrent feedback is most effective. However, feedback can also be disruptive. Bug-in-the-eye (BITE) technology was developed to enable supervisors to provide live feedback to trainees in a minimally disruptive manner by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…Reviews and meta-analyses are methods for collating the empirical evidence based on pre-determined eligibility criteria, in order to address a specific research question (Moher et al, 2009). To the best of our knowledge, there are four reviews on LS (Champe & Kleist, 2003;Gallant & Thyer, 1989;Jakob et al, 2013;Vezer, 2021). Gallant and Thyer (1989) reviewed 15 publications on BITEar supervision .…”
Section: The Evidence In Support Of Live Supervision and Previous Rev...mentioning
confidence: 99%
See 2 more Smart Citations
“…Reviews and meta-analyses are methods for collating the empirical evidence based on pre-determined eligibility criteria, in order to address a specific research question (Moher et al, 2009). To the best of our knowledge, there are four reviews on LS (Champe & Kleist, 2003;Gallant & Thyer, 1989;Jakob et al, 2013;Vezer, 2021). Gallant and Thyer (1989) reviewed 15 publications on BITEar supervision .…”
Section: The Evidence In Support Of Live Supervision and Previous Rev...mentioning
confidence: 99%
“…Vezer (2021) summarized seven studies on BITEye (2000–2018). Despite some methodological problems relating to the studies (e.g., small samples), they concluded that BITEye is generally acceptable, nondisruptive, and has no negative effects on the alliance.…”
Section: The Origin and Rationale Behind Live Supervisionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, supervisors who are assisting an in-person or telehealth session through a live feed can provide immediate feedback to trainees, which is presented in a visual format appearing on a computer screen that is only visible to trainees. A critical review conducted by Vezer (2021) found that the limited number of studies investigating this supervision approach suggest it may enhance supervision outcomes, such as training adherence and clinical competence, without hindering the working alliance.…”
Section: The Introduction Of Technology To Psychotherapy Supervision ...mentioning
confidence: 99%